Rethinking delivery modalities in conflict-affected settings: Why beneficiaries in Sudan prefer digital transfers - Abay, Kibrom A.; Abushama, Hala; Mohamed, Shima; Siddig, Khalid (International Food Policy Research Institute, 2025)
The recent surge in armed conflicts across Africa is increasing demand for humanitarian and social assistance, creating significant pressure on humanitarian actors to deliver life-saving support amid insecurity and constrained resources. The conflict that erupted in Sudan in April 2023 between the Sudanese Armed Forces (SAF) and the Rapid Support Forces (RSF) has resulted in the world’s largest displacement crisis, triggering an acute and multidimensional humanitarian emergency requiring urgent and substantial international support. These armed conflicts in Africa are threatening important gains in poverty reduction made in the last few decades.